Flexibilização do ensino médio no Brasil: impactos e impasses na formação filosófica dos licenciados - Costa, Alana Gabriela Vieira Alvarenga da (2018)
The present work is linked to the research line of Culture and Educational Processes of the Graduate Program in Education (FE / UFG) and analyzes the reform of secondary education by exploring, as the main subject, a flexibilization of the disciplines of human beings, more specifically, the philosophy. Outlining how this reform occurred and what is the purpose of such changes, highlighting the constant conflicts and reformulations around high school in Brazil. Besides, it presents the relationship between the aforementioned reform and the training of graduates, aiming to show that the presence of philosophical knowledge in this area is extremely important for the construction of critical and reflexive thinking, essential skills for teacher training and, in spite of this, subjugated. In the light of the concept of flexible learning that was engendered within the capitalist society that aims to acquire profit and which forms only for the productive world of work, the text discusses how the discipline of philosophy, in its various spheres, went through moments of absence and resistance in the Brazilian educational system. In this sense, based on bibliographic and documental research we verified that documents follow authoritarian trends of forming to reproduction and are far from an humanized formation of subjects. In order to subsidize the discussion and analysis proposed as the objective of this work, the theoretical basis for criticism was based on the following scholars: Carminati (2004), Cerletti (2009), Charle (1996), Coêlho (2006), Gallo (2001), Kohan (2002; 2009), among others.